Erasmus Guillain-Barre Syndrome Outcome Score (EGOS) to predict functional outcomes - Maria Ulfa; Titis Widowati; Agung Triono (Paediatrica Indonesiana, 2022)
Background Guillain-Barre syndrome (GBS) has a highly diverse clinical course and prognosis. Predicting functional  outcomes  is needed in order to give appropriate treatment and counseling. Erasmus Guillaine-Barre Syndrome Outcome Score (EGOS) is simple scoring based on age onset, pre existing diarhea and GDS score obtained from  medical record and physical findings that can be used by clinician to predict the functional outcomes  of the child with GBS..